Memories of a laboratory: Wilhelm Wundt and Experimental Psychology - Alcantarilla, Laura (2023)
The physician, physiologist and psychologist Wilhelm Wundt has been and is considered the founder of experimental psychology due to his approach to psychological subjects, until then intuitive, through the XIX century methods. Thus, a new discipline, the Scientific Psychology, emerged in the venue of a laboratory in the town of Leipzig, Germany. Nevertheless, Wundt´s labor was not restricted to the study of psychology from a scientific perspective: on one hand, his great convocational, organizing and group-working capacity attracted lots of investigators from around the world to be trained. In n original laboratory, On the other, he substantially modified the study of psychology centering the researchers’ attention in the detailed analysis of consciousness through the use of the method called introspection.